Architectural shop drawing of CC5 setting out for ST9 (RFA-225_Rev B) - BUCG-ABC Joint Venture (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.